KONSTRUKSI SOSIAL BERITA KORUPSI BENIH LOBSTER EDHY PRABOWO PADA MEDIA ONLINE (REVIEW ATAS EMPAT MEDIA ONLINE PERIODE TAHUN 2020-2022) - Adi Setiawan, Candra; Nugroho, Adi; Qurrota Ayun, Primada (Interaksi Online, 2024)
This research is based on the existence of many corruption cases in Indonesia, especially in government circles. This research specifically aims to find out how the framing analysis is based on social construction regarding the lobster seed corruption case carried out by Edhy Prabowo. This research was conducted qualitatively using the framing method. The data used in this research is observational analysis of 4 news media. This research analysis uses social construction theory from Burgan Bungin. The results of this research are that the main component of delivering or disseminating messages is mass media. Viewers who read or see it can gain knowledge from the material presented. Thus, different media cannot create and understand reality in different ways. On tempo.co, this news emphasizes that Edhy has received the money and must be given sanctions for this mistake. So this news highlights the punishment for Edhy as a suspect in a corruption case. In the media, people's minds show that the news focuses on the allegations made against Edhy Prabowo regarding the corruption of lobster seeds due to the KPK's arrest activities so that Edhy Prabowo is ready to be sentenced to death as a result of these allegations. CNBC focuses on the involvement of Edhy Prabowo in the lobster seed case with large numbers so that the numbers are the focus of this news. Detik.com focuses on who is involved in this news. That means, okay The content and media technology devices themselves provide a kind of set of beliefs for the audience including effects and impacts.